Are algae ready to take off? GHG emission savings of algae-to-kerosene production. (15th December 2021) - Prussi, M.; Weindorf, W.; Buffi, M.; Sánchez López, J.; Scarlat, N.
Highlights: Sustainable aviation needs liquid fuels, and feedstock availability is crucial. Algae to kerosene is today one of the few certified pathway. An assessment of the GHG saving has been performed, using CORSIA methodology. GHG saving can be up to 68%, for the best case scenario. Nutrients and energy used for production are crucial to produce a sustainable aviation fuel. Abstract: Aviation alternative fuels are perceived as an effective short-term mean to decarbonise our flights. Sustainable aviation fuels from algae have been recently approved for commercial flights, and here we present an assessment of their greenhouse gas (GHG) savings. Three case studies have been investigated with different plant designs and cultivation strategies. The Carbon Offsetting and Reduction Scheme for International Aviation's Life Cycle Assessment methodology is used as a guideline to assess the GHG saving potential of aviation fuels from algae. The approach here presented allows having a sound comparison with other alternative fuel production pathways. We show that the cultivation strategy based on oil maximisation does not necessarily provide significant advantages in terms of GHG savings. The assessed GHG savings fall in a wide range, being dependent on the inputs and cultivation strategy considered. In the best-case scenario, up to 68% of GHG savings can be achieved, therefore offering a substantial advantage over traditional fuels. When compared with the GHG saving of kerosene from other traditional bio-based feedstocks, like rapeseed, the results confirm algae as an interesting alternative, provided that certain conditions for their cultivation, such as high process optimisation, nutrient recycling and use of renewable energy to meet input demand, are met. The study also assessed the area potentially needed for an algae production plant able to supply large volumes of raw material to an existing commercial biorefinery. The findings confirm the potential of this feedstock to mitigate land abandonment on the coasts of the Mediterranean basin.